FACTORS RELATED TO PREEKLAMPISA CASE ON PREGNANT MOTHER IN PUBLIC HEALTH CENTER MADIUN CITY - Dwi Puryani; Lintang Dian Saraswati; M. Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Preclampsia is blood pressure increasing of at least 140/90, proteinuria, and edema. The incidence of preeclampsia continues increasing in worldwide, and cause the death of around 50,000 per year worldwide. In Indonesia, preeclampsia occurs less over 5%, while in Madiun in 2014 (5%) is less 10% than the previous year.The purpose of this study was to determine the factors associated with preeclampsia. Type of this research is analytic observational with cross sectional design. Subjects in this study are 100 respondents of pregnant women trimester II and III. This research will look at the factors of maternal age, age of pregnancy, parity, physical activity, consumption of sodium, fat consumption, economic status, level of knowledge as a risk factor preeclampsia. Univariate analysis shows 57% and 43% of pre-eclampsia no preeclampsia. Bivariate analysis using Chi Square with a significance level of 5%, shows that the parity ( p = 0.032), the level of knowledge (p = 0.000) so that there is a relationship which significantly related with the incidence of preeclampsia. There should be counseling to all midwives and pregnant women to reduce the incidence preeclampsia.